2010
DOI: 10.3109/01674821003793038
|View full text |Cite
|
Sign up to set email alerts
|

Maternal reactions to two-dimensional compared to three-dimensional foetal ultrasonography

Abstract: Our objective was to quantitatively compare maternal reactions to viewing a three-dimensional (3D) ultrasound image of the foetal face to a traditional two-dimensional (2D) sonographic image. One hundred and twelve pregnant women were asked to evaluate their excitement, relief, amazement and satisfaction reactions to 2D and 3D ultrasound images of their foetus' face. A weighted kappa Cochran-Armitage trend test, Fisher exact test and generalised estimating equations were used to analyse the data obtained. 3D i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…No additional effect of 3D and/or 4D on bonding was described. Four studies evaluated ‘feeling of closeness to the fetus’ or ‘relation towards the fetus’ that we considered as a measure of bonding . Three of these studies included the third trimester, and no additional effect of 3D and/or 4D on bonding was described .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No additional effect of 3D and/or 4D on bonding was described. Four studies evaluated ‘feeling of closeness to the fetus’ or ‘relation towards the fetus’ that we considered as a measure of bonding . Three of these studies included the third trimester, and no additional effect of 3D and/or 4D on bonding was described .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated ‘feeling of closeness to the fetus’ or ‘relation towards the fetus’ that we considered as a measure of bonding . Three of these studies included the third trimester, and no additional effect of 3D and/or 4D on bonding was described . Only one study found that mothers after 3D US at 28 weeks felt closer to the baby than after 2D US at 18 weeks …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Several publications have stressed the importance of 3D/4D US in increasing maternal-fetal bonding and even helping in reducing potentially harmful behavior, such as smoking during pregnancy. 34,35 However, others have stated that when comparing 3D/4D with traditional 2D, recognition of fetal anatomy by the mothers-to-be was, indeed, improved but bonding was not better, 36,37 and there was no benefit in terms of anxiety reduction in pregnancies at risk of fetal abnormalities. 38 In addition, even assuming an improvement in maternal-fetal bonding, there are no studies showing benefits to the fetus.…”
Section: Clinical Application Of 3d/4d Ultrasound In Prenatal Diagnosismentioning
confidence: 93%